Relationships among man, environment and sediment transport: A spatial approach - Mahé, Gil; Aksoy, Hafzullah; Brou, Yao; Meddi, Mohamed; Roose, Eric (Revue des sciences de l’eau / Journal of Water Science, 2013)
In the Mediterranean the environment is under pressure from agricultural and urban development, changes in agricultural practices and international markets, and climate change. Moreover, many studies show a steady increase in the agro-pastoral pressure and land degradation and their impacts on water resources and soil, and ultimately the lives of local people. But few studies address these issues across the inclusive scale of large river basins. The conference held at Tipaza in Algeria, from which come several papers published in the Journal of Water Science in 2013, was intended to reflect on the topics, methods and tools available to study the relationships among humans, the environment and sediment transport at this large scale, with the result expected to improve the potential for dialogue between researchers and developers who make decisions for regional macro surfaces. The topics discussed at the conference that appear in the articles published here concern the factors responsible for the variability of sediment transport: climate change and anthropogenic changes, such as agricultural activity and water projects; relationships between land-cover/land-use, rainfall-runoff processes and sediment transport; modeling of sediment transport; and the interest of a multi-scale approach, predominantly a spatial one, for addressing the geographical realities of large basins and scale transfer issues, particularly in Mediterranean and semi-arid areas.